Tax compliance of MSME’s taxpayer: Implementation of theory of planned behavior - Putra, Afuan Fajrian; Osman, Amir Hakim bin (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2019)
This research is aimed to examine the factors that influence the compliance behaviour of MSME’s taxpayer. The variables refer to the theory of planned behaviour, which are attitude towards behaviour, subjective norms and perceived behavioural control that later its influence will be tested towards compliance behaviour in settling the tax. This research will test those factors simultaneously or partially. This research employed population of entire MSMEs that registered in The Cooperation Agency, Small and Middle Enterprises in Sleman Regency, Indonesia. While, the number of samples are obtained by employing slovin formula, which is 100 respondents that cover eight groups of business sector. Questionnaire is applied as data collection technique that employs data analysis method by applying multiple regression and SPSS version 16 as analysis tools. This research indicates that attitude towards behaviour, subjective norms, and perceived behavioural control, simultaneously and significantly influence the compliance behaviour of MSME’s taxpayer. Partially, variable of subjective norms and perceived behavioural control positively influence compliance behaviour of taxpayers in fulfilling their obligation in accomplishing the tax. While the variable of attitude towards behaviour is not positively influence the behaviour of taxpayer’s compliance.